A mineralized hydrogel material based on mussel mucin and its preparation method and application
By constructing a fusion protein of mussel mucin and amyloid, and using silver nanoparticles to biomineralize, a mineralized hydrogel material with good viscosity and mechanical properties was prepared, which solved the problems of low yield, high cost and lack of antibacterial properties of existing materials, and achieved efficient preparation and widespread application of biomedical materials.
Patent Information
- Application Number
- CN202310400977.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-14
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-04-14
AI Technical Summary
The existing mussel mucin-based hydrogel materials have low yields, high cost, complex extraction processes, and lack good antibacterial properties, which limit their application in the field of biomedical science.
By constructing a fusion protein of mussel mucin and amyloid and using silver nanoparticles to biomineralize, a mineralized hydrogel material with good viscosity and mechanical properties was prepared. This material can effectively inhibit bacterial proliferation and promote cell adhesion, migration and proliferation.
It has achieved efficient preparation of hydrogel materials, has good biocompatibility, degradability and antibacterial properties, can promote wound healing, and has broad application prospects.
Smart Images

Figure CN116535866B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a mineralized hydrogel material based on mussel mucin, and a preparation method and application thereof. Background Art
[0002] Due to the widespread use of antibiotics, multidrug-resistant organisms (MDROs) are increasing and mainly appear in hospitals and other medical environments, making secondary infections in clinical operations and wound infections in patients with underlying metabolic diseases such as diabetes face severe challenges. Traditional medical dressings are mostly made of inert materials such as cotton, linen and absorbent cotton gauze with a broader spectrum of antibiotics added. Not only do they have no obvious long-term promoting effect on wound surface and wound healing, they may also lead to the generation of super bacteria.
[0003] In recent years, hydrogel materials have been widely used in the biomedical field due to their good biocompatibility and water retention. They have gradually developed into a new type of medical dressing with good application prospects. Currently, there are two main methods for preparing hydrogels: one is organic polymer chemical cross-linking, such as polyvinyl alcohol hydrogel; the other is natural polymers, such as cellulose hydrogel materials.
[0004] However, organic synthetic polymer hydrogel materials usually have poor biocompatibility, strong immunogenicity, high potential toxicity and require further functional modification and modification. Natural polymers are widely present in nature and have good biocompatibility and degradability. They are ideal raw materials for preparing hydrogels. Mussel mucin, as a natural adhesive protein, can firmly fix shellfish on rocks and ships in a relatively complex seawater environment, showing good adhesion and mechanical support strength. Therefore, the development of new hydrogel materials based on mussel mucin is widely used in the biomedical field. For example, Corning currently develops Ce ll-Tak cell adhesive has better cell adhesion properties than traditional gelatin or polylysine. However, the current hydrogel materials based on mussel mucin are mainly extracted from natural mussels. Only about 1g of Cell-Tak products can be produced for every 10,000 mussels. The yield is low, the cost is high, and the extraction process is complicated, which greatly limits its application in the biomedical field. In addition, natural mussel mucin does not have good antibacterial properties, which greatly limits its application. Therefore, it is necessary to develop a hydrogel material that has the advantages of existing medical hydrogels and good antibacterial properties. Summary of the invention
[0005] The purpose of the present invention is to provide a mineralized hydrogel material based on mussel mucin and its preparation method and application in order to solve the above problems. The mineralized hydrogel material has good viscosity and mechanical properties; can effectively induce oxidative stress response of Gram-positive and Gram-negative bacteria, inhibit bacterial proliferation; can promote cell adhesion, migration and proliferation, and contribute to wound healing.
[0006] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0007] A mineralized hydrogel material based on mussel mucin. The mineralized hydrogel material is obtained by biomineralizing and incubating a protein solution with silver nanoparticles. The protein solution includes at least one fusion protein, and the fusion protein is obtained by recombining mussel mucin and amyloid protein.
[0008] As a further optimization scheme of the present invention, the mussel mucin is any one or more of Mfp3, Mfp5 (from Mytilus galloprovincialis), Pvfp5β (from Asian green mussel Perna viridis), and the amyloid protein is a polypeptide sequence in yeast prion protein Sup35, as specifically shown in SEQ ID NO.4.
[0009] As a further optimization scheme of the present invention, the fusion protein includes Mfp3-Sup35, Mfp5-Sup35 and Pvfp5β-Sup35.
[0010] As a further optimization scheme of the present invention, the mineralized hydrogel material includes any one fusion protein of Mfp3-Sup35, Mfp5-Sup35, Pvfp5β-Sup35 or two fusion proteins of Pvfp5β-Sup35 and Mfp3-Sup35.
[0011] A method for preparing a mineralized hydrogel material based on mussel mucin comprises the following steps:
[0012] (1) transforming the fusion protein obtained by in vitro construction and recombination of mussel mucin and amyloid protein into Escherichia coli; centrifuging the induced expression bacterial solution at 6000 rpm / min to collect the bacterial cells; resuspending the collected bacterial cells in a buffer solution, and performing ultrasonic disruption to obtain a disrupted suspension;
[0013] (2) The crushed suspension was purified using a Ni-NTA affinity chromatography column, and impurities were first washed away with a low concentration of imidazole (20 mM) buffer, and then treated with tyrosinase for 2 h, and then the target protein was eluted with a 250 mM imidazole buffer to obtain a crude purified protein solution; the crude purified protein solution was dialyzed multiple times with different buffers to obtain a renatured protein solution; the renatured protein solution was freeze-dried to obtain a protein dry powder;
[0014] (3) dissolving the protein powder with sodium citrate buffer to obtain a mixed protein solution;
[0015] (4) Add silver nitrate to the mixed protein solution and incubate to obtain a mineralized hydrogel material.
[0016] As a further optimized solution of the present invention, in step (1), the Escherichia coli is E. coli BL21 (DE3), and the expression conditions are 0.4 mM IPTG, 20° C. induction for 16 h.
[0017] As a further optimization scheme of the present invention, in step (1), the resuspension buffer is PBS buffer pH 7.4 (8M urea, 20mM imidazole, 1mg / mL lysozyme and 1mM PMSF), and the ultrasonic disruption condition is 45% power, running for 2s and pausing for 4s.
[0018] As a further optimization scheme of the present invention, in step (2), the tyrosinase concentration is 0.5 mg / mL.
[0019] As a further optimization scheme of the present invention, in step (2), the affinity chromatography is Ni-NTA affinity chromatography, the dialysis buffer is PBS pH7.4 buffer (2M urea), PBS pH7.4 buffer, ultrapure water, and 5% acetic acid in sequence, the dialysis condition is 4°C, the volume ratio of protein solution to dialysate is 1:100, and dialysis is performed twice.
[0020] As a further optimization scheme of the present invention, in step (2), the freeze-drying conditions are -60°C to -80°C, vacuum degree to 15 Pa, and 24 hours.
[0021] As a further optimization scheme of the present invention, in step (3), the concentration of the sodium citrate buffer is 0.1 M, the pH is 5.5, and the concentration of the mixed protein solution is 2-5 mg / mL.
[0022] As a further optimization scheme of the present invention, in step (4), the silver nitrate concentration is 1%, the incubation temperature is 37° C., and the incubation time is 4 to 6 hours.
[0023] Application of a mineralized hydrogel material based on mussel mucin in the preparation of antibacterial materials.
[0024] As a further optimization solution of the present invention, the antibacterial material is a medical dressing material.
[0025] As a further optimization scheme of the present invention, the antibacterial bacteria are Gram-negative and Gram-positive bacteria.
[0026] As a further optimization scheme of the present invention, the Gram-negative and Gram-positive bacteria are any one of Escherichia coli (E. coli), Staphylococcus aureus (S. aureus), Pseudomonas aeruginosa (P. aeruginosa), and Listeria monocytogenes (L. monocytogenes).
[0027] The beneficial effects of the present invention are:
[0028] 1) The present invention utilizes two natural proteins, a fusion protein of mussel mucin and amyloid protein, as structural elements to construct a self-assembled mineralized hydrogel material, wherein mussel mucin has good viscosity, and amyloid protein has good toughness and stability, so that the mineralized hydrogel material has the advantages of both, and has good biocompatibility and degradability, and the amyloid fiber structure enhances the mechanical strength of the hydrogel skeleton, thereby improving the sustained release effect of the mineralized silver nanoparticles;
[0029] 2) The biomineralized hydrogel prepared by the present invention has good biological effects, can promote cell adhesion, proliferation and migration, and has a good slow-release silver ion effect. It utilizes the property that silver ions easily enter bacteria to induce oxidative stress reaction to achieve a bactericidal effect, and can promote wound healing. The hydrogel has good air permeability, which is helpful for wound repair;
[0030] 3) The biomineralized hydrogel material prepared by the present invention has broad development prospects and can be used to prepare wound dressing materials used in clinical practice. The dressing material has the function of preventing wound infection and promoting wound healing. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The photographs of the silver nanoparticles in the hydrogel material of Example 1 before and after mineralization are shown;
[0032] Figure 2 is a TEM image of the hydrogel material of Example 1 before and after mineralization;
[0033] Figure 3 The photographs of the silver nanoparticles in the hydrogel material of Example 2 before and after mineralization are shown;
[0034] Figure 4 is a TEM image of the hydrogel material of Example 2 before and after mineralization;
[0035] Figure 5The photographs of the silver nanoparticles in the hydrogel material of Example 3 before and after mineralization are shown;
[0036] Figure 6 is a TEM image of the hydrogel material of Example 3 before and after mineralization;
[0037] Figure 7 is a graph of rheological properties of mineralized hydrogel materials;
[0038] Figure 8 It is a diagram of the cell growth state of the mineralized hydrogel material;
[0039] Fig. 9 is the cellular activity of the mineralized hydrogel material;
[0040] Fig.10 This is a hemolysis experiment diagram of mineralized hydrogel material;
[0041] Fig.11 This is a flat plate antibacterial effect diagram of the prepared mineralized hydrogel material in Example 1 on Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa and Listeria;
[0042] Fig.12 The prepared mineralized hydrogel material induces peroxidative stress effect on Escherichia coli and Staphylococcus aureus in Example 2;
[0043] Fig.13 This is a diagram showing the effect of the mineralized hydrogel material on Listeria-infected cells in Example 3;
[0044] Fig.14 This is a diagram showing the adhesion and growth promotion effect of the mineralized hydrogel material on human embryonic kidney cells HEK293T in Example 4. DETAILED DESCRIPTION
[0045] The present application is further described in detail below in conjunction with the accompanying drawings. It is necessary to point out here that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technical personnel in this field can make some non-essential improvements and adjustments to the present application based on the above application content.
[0046] 1. Materials
[0047] The methods used in this example are conventional methods known to those skilled in the art unless otherwise specified, and the reagents and other materials used are commercially available products unless otherwise specified.
[0048] 2. Methods
[0049] 2.1 Preparation method of mineralized hydrogel material
[0050] Example 1
[0051] A mineralized hydrogel material based on mussel mucin, which is composed of the fusion protein Pvfp5β-Sup35, and the specific steps are as follows:
[0052] Step 1: Transform the recombinant plasmid Pvfp5β-Sup35 into Escherichia coli, express and purify the fusion protein to obtain freeze-dried powder;
[0053] Step 2: Dissolve the Pvfp5β-Sup35 protein powder in sodium citrate buffer at pH 5.5 to obtain a protein solution with a concentration of 3 mg / mL;
[0054] Step 3: Incubate the protein solution at 37° C. for 4 to 6 hours to obtain an unmineralized hydrogel material, or add 1% silver nitrate solution to the protein solution and incubate at 37° C. for 4 to 6 hours to obtain a mineralized hydrogel material.
[0055] Example 2
[0056] A mineralized hydrogel material based on mussel mucin, which is composed of the fusion protein Mfp5-Sup35, and the specific steps are as follows:
[0057] Step 1: Transform the recombinant plasmid Mfp5-Sup35 into Escherichia coli, express and purify the fusion protein to obtain freeze-dried powder;
[0058] Step 2: Dissolve the Mfp5-Sup35 protein powder in sodium citrate buffer at pH 5.5 to obtain a protein solution with a concentration of 2.0 mg / mL;
[0059] Step 3: Incubate the protein solution at 37° C. for 4 to 6 hours to obtain an unmineralized hydrogel material, or add 1% silver nitrate solution to the protein solution and incubate at 37° C. for 4 to 6 hours to obtain a mineralized hydrogel material.
[0060] Example 3
[0061] A mineralized hydrogel material based on mussel mucin, which is composed of the fusion protein Mfp3-Sup35, and the specific steps are as follows:
[0062] Step 1: Transform the recombinant plasmid Mfp3-Sup35 into Escherichia coli, express and purify the fusion protein to obtain freeze-dried powder;
[0063] Step 2: Dissolve the Mfp3-Sup35 protein powder in sodium citrate buffer at pH 5.5 to obtain a protein solution with a protein concentration of 5 mg / mL;
[0064] Step 3: Incubate the protein solution at 37° C. for 4 to 6 hours to obtain an unmineralized hydrogel material, or add 1% silver nitrate solution to the protein solution and incubate at 37° C. for 4 to 6 hours to obtain a mineralized hydrogel material.
[0065] Example 4
[0066] A mineralized hydrogel material based on mussel mucin, which is composed of fusion proteins Pvfp5β-Sup35 and Mfp3-Sup35, and the specific steps are as follows:
[0067] Step 1: transform the recombinant plasmids Pvfp5β-Sup35 and Mfp3-Sup35 into Escherichia coli respectively, express and purify the fusion protein powder to obtain freeze-dried protein;
[0068] Step 2: Dissolve the Pvfp5β-Sup35 and Mfp3-Sup35 protein powders in a pH 5.5 sodium citrate buffer at a ratio of 3:1 to obtain a mixed protein solution with a concentration of 5 mg / mL;
[0069] Step 3: Incubate the mixed protein solution at 37° C. for 4 to 6 hours to obtain an unmineralized hydrogel material, or add 1% silver nitrate solution to the mixed protein solution and incubate at 37° C. for 4 to 6 hours to obtain a mineralized hydrogel material.
[0070] The protein sequences of the above-mentioned Mfp3, Mfp5, Pvfp5β and Sup35 are shown in Table 1:
[0071] Table 1
[0072]
[0073] 2.2 Morphology and morphology of mineralized hydrogel materials
[0074] The hydrogel material and the mineralized hydrogel material prepared in Example 1 were macroscopically observed. Figure 1 At the same time, the hydrogel material and the mineralized hydrogel material prepared in Example 1 were negatively stained and placed under a transmission electron microscope to observe and compare their microscopic morphologies, and high-resolution imaging of the silver nanoparticles on the mineralized hydrogel material was performed to analyze the lattice parameters. The results are shown in Figure 2 .
[0075] Experimental conclusion: Figure 1 It can be seen that the unmineralized hydrogel material ( Figure 1 a) is in a milky white semi-solid state, and the prepared mineralized hydrogel ( Figure 1 b) presents a light yellow-brown transparent semi-solid state, the color mainly comes from the in-situ mineralized silver nanoparticles; Figure 2 It can be seen that the surface of the unmineralized hydrogel fiber is smooth and flat, with a network structure ( Figure 2 a), while the mineralized hydrogel material has many nanoparticles of about 5 nanometers attached in addition to the nanofiber network structure ( Figure 2b), high-resolution TEM results show that the lattice size of the nanoparticles is 0.235nm, which is a typical silver nanoparticle crystal structure; at the same time, the hydrogel and mineralized hydrogel materials prepared in Examples 2-3 also have the above-mentioned morphology and morphology, as shown in detail Figure 3-6 shown.
[0076] 2.3 Rheological test of mineralized hydrogel materials
[0077] The prepared mineralized hydrogel material was subjected to rheological tests in the angular frequency-dependent oscillatory rheological shear mode, with a strain rate of 5% and an angular frequency of 1 to 100 rad / s. The test results are shown in Figure 7 , strain rate is 5%, angular frequency is 10rad / s, and the test results are shown in Table 2.
[0078] Table 2 (strain rate is 5%, angular frequency is 10rad / s)
[0079]
[0080] Experimental conclusion: Figure 7 As shown in Table 2, the mineralized hydrogel material has good storage modulus G' and loss modulus G", when the strain rate is 5% and the angular frequency is 10rad / s, G' and G" are 21.2Pa and 6.7Pa respectively, showing good mechanical properties. In addition, the mineralized hydrogel material also exhibits good viscosity, up to 445mPa·s (strain rate is 5%, angular frequency is 10rad / s).
[0081] 2.4 Biocompatibility test of mineralized hydrogel materials
[0082] Inoculate ~10 cells per well of a 96-well plate 4 After culturing for 24 hours, different concentration gradients (5-100 μM) of mineralized hydrogel materials were added, and the wells without any treatment were used as blank controls. After continuing to culture for 24 hours, 48 hours and 72 hours, the cells were placed under a microscope to observe the cell morphology. The results are shown in Figure 8 At the same time, MTT reagent was used to detect cell activity. The results are shown in Fig. 9 .
[0083] Experimental conclusion: Figure 8 and Fig. 9 It can be seen that after adding the mineralized hydrogel material Ag@Hydrogel, the cells still maintain a good growth state and cell morphology at a concentration of up to 100μM, indicating that the mineralized hydrogel material has good biocompatibility.
[0084] 2.5 Hemolytic properties of mineralized hydrogel materials
[0085] The mineralized hydrogel material Ag@Hydrogel of the vegetation in Example 1 was added to the sheep red blood cell solution and allowed to stand for 1 hour. 10 μL of the treated sheep red blood cell solution was taken and observed under a microscope. The sheep red blood cells without any treatment were used as blank controls, and the samples treated with 0.1% Triton X-100 were used as positive controls. The results are shown in Fig.10 .
[0086] Experimental conclusion: Fig.10 It can be seen that the prepared mineralized hydrogel material Ag@Hydrogel failed to induce hemolysis of sheep erythrocytes, indicating that it has good biocompatibility and may be used in the treatment of human wound infection healing.
[0087] 2.6 In vitro antibacterial test of mineralized hydrogel materials
[0088] The frozen strains of Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Listeria monocytogenes were inoculated into 5 mL of fresh culture medium and cultured in a shaker at 37 °C and 220 rpm for 16 h. The bacterial concentration after culture was adjusted to OD 600 The concentration of the hydrogel material was 0.1, 10 μL of the mineralized hydrogel material was added to 100 μL of the above bacterial solution, and the solution was incubated at 37°C for 1 h. The solution without the addition of the mineralized hydrogel material was used as the blank control. The bacterial solution after incubation was diluted 10,000 times, and 100 μL of the diluted bacterial solution was spread on the plate. After culturing at 37°C for 24 h, the colony morphology was observed, the colony count was performed (Listeria was cultured for 48 h), and photographed and recorded. The results are shown in Fig.11 .
[0089] Experimental conclusion: Fig.11 It can be seen that compared with the unmineralized hydrogel material Hydrogel, the silver nanoparticle mineralized hydrogel material Ag@Hydrogel has a significant inhibitory effect on both Gram-negative and Gram-positive bacteria.
[0090] 2.7. Experiment on bacterial ROS induced by mineralized hydrogel materials
[0091] In order to further explore the bactericidal mechanism of mineralized hydrogel materials and the effect of silver ion release, Escherichia coli and Staphylococcus aureus were cultured overnight, and the bacterial concentration after culture was adjusted to OD 600The concentration of H2DCFDA was 0.1, 100 μL of the above bacterial solution was added with 10 μL of mineralized hydrogel material, and incubated at 37°C for 1 h. The blank control was made without adding mineralized hydrogel material. The incubated bacterial solution was centrifuged at 5000 rpm for 5 min, the supernatant was discarded, and the bacteria were resuspended with 10 μM H2DCFDA. After incubation at room temperature and away from light for 30 min, the solution was centrifuged at 5000 rpm for 5 min, the supernatant was discarded, and the bacteria were resuspended with water to wash away the excess H2DCFDA, and finally resuspended with 100 μL of water; 10 μL of the above resuspension was placed in the center of the slide, and after natural drying, it was placed under a fluorescent inverted microscope for observation. The results are shown in Table 1. Fig.12 .
[0092] Experimental conclusion: Fig.12 It can be seen that the mineralized hydrogel material induces bacterial death mainly by inducing oxidative stress response in Escherichia coli and Staphylococcus aureus, producing excessive oxygen free radicals that oxidize H2DCFDA into green fluorescent dye.
[0093] 2.8. Mineralized hydrogels inhibit Listeria infection in human embryonic kidney cell line HEK293T cells
[0094] 200 μL of mineralized hydrogel material and unmineralized hydrogel material were added to the bottom of the six-well plate for coating. After 1 hour, the excess hydrogel material was removed and the wells without any treatment were used as blank controls. 10 cells were inoculated in each well. 5 cells. After culturing for 24 hours, remove the culture medium, wash one side with PBS buffer, add Listeria for infection, and the infection multiplicity MOI is 0.1. After 1 hour of infection, wash it again with PBS, sterilize it with 100μg / mL gentamicin sulfate, wash it again with PBS, and culture it with a culture medium containing 25μg / mL gentamicin sulfate for 24 hours; aspirate the culture medium containing gentamicin sulfate, add 1mL PBS buffer to wash, add 1mL of cell lysis buffer to lyse for 1 hour, and then transfer it to a 1.5mL EP tube, dilute the lysate gradient into 10-fold, 100-fold, and 1000-fold solutions, take 100μL from the 1000-fold dilution to plate, and set up three parallels, culture at 37℃ for 24 hours, observe the colony morphology and count them, and the results are shown in the figure. Fig.13 .
[0095] Experimental conclusion: Fig.13 It can be seen that the number of colonies produced by the cell lysate coated with mineralized hydrogel material after culture is much smaller than that of the untreated cell and that of the cell lysate treated with silver nanoparticles. This shows that the mineralized hydrogel material has good adhesion, can effectively adhere to the surface of the matrix, and release silver ions for a long time, effectively killing Listeria and preventing Listeria from infecting cells, and the antibacterial effect is better than that of the single application of silver nanoparticles.
[0096] 2.9. Experiment on the promotion of cell adhesion and proliferation by mineralized hydrogel materials
[0097] Mussel mucin has abundant DOPA groups and positively charged amino acids, so it has good adhesion properties and can be used as a good cell adhesion agent to promote cell proliferation and migration. To this end, we further explored the effect of mineralized hydrogel materials on cell proliferation. The specific steps include: using the mineralized hydrogel material prepared above to coat the 96-well plate, removing the excess hydrogel material after 1 hour, using the wells without any coating as blank controls, inoculating 3000 to 5000 cells in each well, culturing for 6 hours, removing the culture medium and the cells that are not attached, and detecting cell activity with MTT reagent; at the same time, the cells were fixed with 0.25% paraformaldehyde, permeabilized with 0.1% Triton X100, and then incubated with anti-actin antibody for 1 hour, and blocked with 1% BSA for 1 hour, and finally incubated and stained with goat anti-rabbit secondary antibody with red fluorescent label for 1 hour, removing the excess dye and washing with PBS buffer, and finally stained with DAPI for 10 minutes, and then observed under an inverted fluorescence microscope. The results are shown in Fig.14 .
[0098] Experimental conclusion: Fig.14 It can be seen that both mineralized and unmineralized hydrogel materials can significantly enhance cell adhesion and wall attachment, and can effectively promote the formation of cell skeletons and cell migration; Examples 2 to 3 also have the above effects of Example 1.
[0099] In summary, the mineralized hydrogel material prepared by the present invention has good adhesion and mechanical support properties, can overcome the shortcomings of traditional dressing materials, and has good air permeability and water retention. In addition, the mineralized loaded silver nanoparticles have good sustained-release properties and achieve good long-term antibacterial properties; compared with traditional antibiotics, it has a broad spectrum of antibacterial properties. Therefore, the biomineralized hydrogel material prepared by the present invention has broad application prospects.
[0100] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A mineralized hydrogel material based on mussel mucin, characterized in that: The mineralized hydrogel material is obtained by subjecting a protein solution to biomineralization and incubation of silver nanoparticles, wherein the protein solution includes at least one fusion protein, and the fusion protein is obtained by reconstructing and recombining mussel mucin and amyloid protein; Wherein, the mussel mucin is any one or more of Mfp3, Mfp5, and Pvfp5β, the polypeptide sequences of the mussel mucins Mfp3, Mfp5, and Pvfp5β are shown in SEQ ID NO.1-3, respectively, and the amyloid protein is a polypeptide sequence in yeast prion protein Sup35, specifically shown in SEQ ID NO.4; Wherein, the protein solution is obtained by dissolving fusion protein powder in sodium citrate buffer; The mineralized hydrogel material is obtained by adding 1% silver nitrate solution into a protein solution and incubating the solution.
2. A mineralized hydrogel material based on mussel mucin according to claim 1, characterized in that: The fusion proteins include Mfp3-Sup35, Mfp5-Sup35 and Pvfp5β-Sup35.
3. A mineralized hydrogel material based on mussel mucin according to claim 2, characterized in that: The mineralized hydrogel material comprises any one fusion protein of Mfp3-Sup35, Mfp5-Sup35, Pvfp5β-Sup35 or two fusion proteins of Pvfp5β-Sup35 and Mfp3-Sup35.
4. A method for preparing a mineralized hydrogel material based on mussel mucin according to any one of claims 1 to 3, characterized in that: The steps include: (1) expressing the fusion protein in Escherichia coli to obtain a crude protein solution; (2) The crude protein solution is subjected to affinity chromatography and multi-step dialysis, and then freeze-dried to obtain protein dry powder; (3) dissolving the protein powder with sodium citrate buffer to obtain a mixed protein solution; (4) Add silver nitrate to the mixed protein solution and incubate to obtain a mineralized hydrogel material.
5. The method for preparing the mineralized hydrogel material based on mussel mucin according to claim 4, characterized in that: In step (1), the expression conditions of the Escherichia coli are 0.4 mM IPTG, 20° C. induction for 16 h, in step (3), the concentration of the sodium citrate buffer is 0.1 M, the pH is 5.5, the concentration of the mixed protein solution is 2-5 mg / mL, and in step (4), the concentration of the silver nitrate is 1%, the incubation temperature is 37° C., and the incubation time is 4-6 h.
6. Use of the mineralized hydrogel material based on mussel mucin as claimed in any one of claims 1 to 3 in the preparation of antibacterial materials.
7. The use according to claim 6, characterized in that: The antibacterial material is a medical dressing material.
8. The use according to claim 7, characterized in that: The antibacterial bacteria are Gram-negative and Gram-positive bacteria.
9. The use according to claim 8, characterized in that: The Gram-negative and Gram-positive bacteria are any one of Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Listeria.
Citation Information
Patent Citations
Synthetic hybrid spidroin-amyloid-mussel foot protein for underwater adhesion of diverse surfaces
WO2022046932A2